Correlation Ofmaternal Serum Ferritin With Cord Blood Dopamine Concentration - Wulan Dewi Rizky; Vaulinne Basyir; Rima Semiarty (Journal of Midwifery, 2018)
Anemia in pregnancy is a common health problems today, where iron deficiency is the main cause. Iron deficiency will affect the various organs and metabolic pathways, especially the central dopamine pathway. Dopamine is a neurotransmitter that is found in brain and affects human interpersonal actions and correlations. The purpose of this study was to determine the correlation of maternal serum feritin with cord blood dopamine concentration. The design of this study was cross sectional, observe 30 pregnant women with their babies born in Rika Hardi, SSiTmaternity clinic. Samples were selected by consecutive sampling. Ferritin and dopamine concentration was checked at BalaiLaboratoriumKesehatan West Sumatera, where ferritin concentration by ECLIA and dopamine concentration by ELISA. Data were analyzed with Spearman correlation test to find the correlation of maternal serum feritin with cord blood dopamine concentration. The study results obtained, mean concentration of maternal serum ferritin 33,21±26,08 ng/mL and cord blood dopamine concentration 172,27±27,21 ng/L. Correlation test of maternal serum feritin with cord blood dopamine concentration had p value = 0,301 (p>0,05). In this study, we can conclude that there is no correlation between maternal serum feritin with cord blood dopamine concentration.Further research is needed by considering various factors that affect maternal ferritin concentration such as food intake and iron supplementation, and which affect dopamine concentration, such as stress and adequate sleep.